Building construction labour productivity in arid climate environment - Bhatti, Imtiaz Ali; Abdullah, Abd Halid; Nagapan, Sasitharan; BHATTI, Nabi Bux; Lakhiar, Muhammad Tahir; MAHAR, Muntazir Mahdi (Sciendo, 2019)
Productivity is a significant aspect of construction industry that plays vital role for success and failure of any construction project. This industry generates 11% to 13% of GDP all around the globe and the cost of labour in any building project is 20% to 35% of the cost of Building. On daily basis labour utilizes 30% of time on productive activities rest 70% of the time is ruined in non-productive activities, there are multi factors which are affecting the labour production in construction industry hence this study provides an overview of productivity, Total Factor productivity, method used to measure accurate productivity in construction projects. The objective of this study is find out percentage up to what extent labour production is affected due to weather conditions, however this study is carried out in arid climate region in Month of June 2018, where minimum temperature was recorded 26.0 Celsius degree at 7:30 AM and Maximum was 47.80 Celsius degree at 3:00 PM. A descriptive survey research design approach was adopted using continuous observation method of study. Project work study manual served as the research instrument to collect the data on selected building sites for 30 working days. Data collected were analyzed using descriptive statics. The results show that average monthly production of mason gang was recorded with less production of 28.759%, Carpentry gang with average monthly loss of production 16.74% & steel fixer gang had average monthly loss of production was 12.188. This concludes that prior to signing the contract for construction project. The location, environment, topography of region, capacity of construction operatives must be kept in mind to decide the proper timeline for the successful of project.